Enhanced phytase production by Aspergillus niger mutants in solid state fermentation: DOI: 10.48129/kjs.15995 - Mahmood, Shahzad; Memuna G. Shahid; Muhammad Nadeem; Rubina Nelofer; Muhammad Irfan (Kuwait Journal of Science, 2023)
The present research work was conducted to improve the phytase production by genetic alteration of Aspergillus niger with induced mutagenesis using solid state fermentation. Strain improvement was carried out in the presence of ultra violet (UV) irradiation and ethyl-methane sulphonate (EMS) (0.5% v/v) treatments for various time intervals. We reported an improved strain of Aspergillus niger designated as UV-3 mutant producing a zone of hydrolysis of about 40 mm, in comparison to parent strain (26 mm). The highest enzyme activity was found to be 547.64 IU/g for UV-3 mutant compared to parent strain which showed 406.45 IU/g of enzyme activity. Thus, physical and chemical mutagenesis was proved as an effective technique for the improvement of strain and ultimately for enhanced and economical phytase production for different industrial applications.